Multi-scale models for CO₂ injection into deep saline aquifers - abstract - Celia, Michael A., author; Colorado State University, publisher (Colorado State University. Libraries, 2012)
Abstract of award lecture "Multi-scale models for CO2 injection into deep saline aquifers" given on March 22, 2012 by Michael A. Celia, winner of the 2012 Hydrology Days Award.
Hydrology days 2012
AGU hydrology days 2012
2012 annual AGU hydrology days was held at Colorado State University on March 21 - March 23, 2012.
Keywords: Hydrology -- Congresses; Award winners